Meningkatkan Hasil Belajar Siswa Sekolah Dasar Menggunakan Model Mind Mapping dan Media Flash Card - Oviana, Wati; Rahmi, Putri; Humairah, Humairah; Jannah, Misbahul (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
Based on the results of initial observations at SD Negeri Lamreung Aceh Besar it is known that some students have not reached the minimum completeness criteria (KKM) that has been determined by the school, namely 69. This study aims to find out how teacher activities, student activities and student learning outcomes are in the learning process using the model mind mapping and flash card media in thematic learning in class V SD Negeri Lamreung Aceh Besar. The research method used is classroom action research. Collecting data in this study used teacher activity observation sheets, student activity sheets and test questions. The data analysis technique used is descriptive qualitative. The results obtained showed that teacher activity in cycle I was 78.44 (good) and increased in cycle II to 91.37 (very good). Student activity in cycle I obtained a score of 73.27 (good) and increased in cycle II to 88.79 (very good). Student learning outcomes in cycle I was 65.21% (enough) and there was an increase in cycle II to 82.60% (very good). The results of this study indicate that the use of mind mapping models and flash card media can improve student learning outcomes in thematic learning.